Riješiti jednačinu u skupu cijelih brojeva

x2 – xy – 2y2 = 7

x2 – xy – 2y2 = 7=> (x – 2y)(x + y) = 7.

*I slučaj

x – 2y = 7

x + y = 1

y=1-x

x-2(1-x)=7

x-2+2x=7

3x-2=7

3x=9

x=3

y=1-x= 1-3=2

(3,-2)

  • II slučaj

x – 2y = 1

x + y = 7

x-2y=1

2x+2y=14

3x=15

x=5

y=7-x

y=2

(5,2)

  • III slučak

x – 2y = –7

x + y = –1;

3y=6

y=2

x+2=-1

x=-3

(-3,2)

  • IV slučaj

x – 2y = –1

x + y = –7.

3y=-6

y=-2

x-2=-7

x=-5

(-5,-2)

Community content is available under CC-BY-SA unless otherwise noted.